Evaluation of keratin templates on dermal regeneration of full-thickness burns - Moay, Zi Kuang (Nanyang Technological University, 2024)
Full-thickness burns presents themselves as damages to both epidermis and dermis, and may affect the subcutaneous tissue, muscular, neurovascular, and skeletal structures. The current gold standard for treating full-thickness burns is skin grafting. While autografts are preferred, they are limited by availability. Allografts are the next best options but face increased risks of immunogenicity. The use of collagen based dermal equivalents such as Integra® and PELNACTM partially alleviates these issues, but they are costly and may not be viable for large burns. Research has shown total hair proteins (THP) as a potential solution to wound treatment due to its abundance, biocompatibility, and angiogenic potential. As a biomaterial, THP can be easily sourced and valorised from human hair waste, thus addressing the issue of increasing human hair waste from hair salons. Various forms of THP templates have yielded good biocompatibility and observable wound healing in both in vitro and in vivo studies, which were largely attributed to the cell binding motifs mimicking those present in the extracellular matrix (ECM). As such, this thesis aims to utilise the wound healing potentials of THP to design a dermal substitute suitable for addressing full-thickness burn wounds. THP is explored as an alternative to dermal substitutes due to its abundance, biocompatibility, and angiogenic potential. Two versions of foams have been designed; the first being a hybrid foam consisting of THPs crosslinked with alginate (KA) using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysulfosuccinimide (sulfo-NHS), while the second consists entirely of human hair keratins (HHK) which relies on its self-assembly properties. Previous works had shown the angiogenic capabilities of KA foams in in vivo mice studies. Herein, both KA and HHK foams were scaled up to simulate their application in an actual skin grafting scenario. Their mechanical properties were measured to understand possible differences owing to the increase in dimensions. A co-culture of telomerase-immortalised microvascular endothelial cells (TIME-EC) and human dermal fibroblasts (HDF) was seeded on HHK foams to better observe the angiogenic properties of the foams in a scenario comparable to that within the skin structure. The performance of both foams as dermal substitutes was also tested on full-thickness burns in a pig burn wound model and evaluated in comparison with PELNACTM (commercial collagen foam) via wound healing parameters including wound size and immunohistochemical stains of dermal markers. Results showed that while larger foams were able to retain similar structural and mechanical properties as their smaller counterparts, HHK foams were more structurally stable than KA foams and thus were chosen for subsequent studies. Seeding HHK foams with a TIME-EC:HDF co-culture revealed that the cells adapted well to the foams, although vessel-like networks were not observed in the foams. In vivo, HHK foams did not impede wound regeneration from full-thickness burns on pig skin. All in all, HHK foams are capable as dermal substitutes to treat full-thickness burn wounds through promoting earlier angiogenesis in the surrounding tissue, though it would require further modifications to improve its potential of being an ideal dermal substitute.